Enzymatic hydrolysis of thermally pre-treated chitin and antimicrobial activity of N,N′-diacetylchitobiose - Z Abidin, Munira; Kourmentza, Constantina; K Karatzas, Andreas; Niranjan, Keshavan (Wiley, 2019)
Background: n,n′-diacetylchitobiose (glc n ac2) is known to be highly functional and offers a wide range of applications, especially as an antimicrobial agent. In this study, a thermal pre-treatment process using steam under pressure in an autoclave was employed to facilitate subsequent enzymatic hydrolysis of chitin with chitinase from streptomyces griseus. Results: pre-treatment of chitin with 0.05mol l−1 sodium acetate buffer (p h= 6.0) at 121 ∘c for 60 min, followed by enzymatic hydrolysis involving24 hincubation,were foundtobethebest conditions for producing glc n ac2. the glc n ac2 thus obtainedwas tested regarding its antimicrobial activity against gram-negative and gram-positive strains and showed minimum inhibitory concentrations at 5 and 10% (w/v) against escherichia coli k-12 and listeria monocytogenes 10403 s, respectively. Conclusions: the extent of swelling and crystallite size of chitin increased with pre-treatment residence time, and enhanced the rate of subsequent hydrolysis using chitinase. © 2019 society of chemical industry